2015
DOI: 10.5772/60530
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the Success and Survival of Entrepreneurs in the Construction Industry

Abstract: A review of entrepreneurship literature suggests that entrepreneurial activities are the most important drivers for economic growth and corporate success, regardless of size, age or industry. Nevertheless, so far, only a few studies, if any, have considered entrepreneurship as a success factor for construction enterprises, although the importance of the construction industry to the nation's economic growth is significant. This paper reports a conceptual framework for formulating the success and survival factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 66 publications
1
22
0
1
Order By: Relevance
“…25 It was also suggested that a positive relationship between entrepreneurial competencies and the success and survival of entrepreneurs exists. 26 Furthermore, through an extensive literature review, it was found that there is a significant and small overall relationship between human capital and entrepreneurial success, and the magnitude of this relationship depends on conceptualizations of human capital, the context of the firm, and the choice of success measures. 8 Prior research has suggested a number of arguments.…”
Section: The Role Of Human Capitalmentioning
confidence: 99%
“…25 It was also suggested that a positive relationship between entrepreneurial competencies and the success and survival of entrepreneurs exists. 26 Furthermore, through an extensive literature review, it was found that there is a significant and small overall relationship between human capital and entrepreneurial success, and the magnitude of this relationship depends on conceptualizations of human capital, the context of the firm, and the choice of success measures. 8 Prior research has suggested a number of arguments.…”
Section: The Role Of Human Capitalmentioning
confidence: 99%
“…An entrepreneurial capability as a distinct set of individual capabilities and skills aim to explore, integrate, and exploit untapped business opportunities within a market context. An entrepreneurial ecosystem as the social and economic environment affects entrepreneurship [14]. Environmental turbulence can have a significant impact on the performance of an organization [15], hence entrepreneurs should have information about whether growth through internal resources is sufficient and in line with the goals and objectives [16].…”
Section: Conceptual Modelmentioning
confidence: 99%
“…So it is important to focus all phases of building construction to understand the factors that affect the quality of project [8][9]. It is also required to elaborate the role of management, quality assurance system and its applications in different aspects [10][11].…”
Section: Introductionmentioning
confidence: 99%